Perspectives of Lélia Gonzalez and Milton Santos on racism and class prejudice: the case of Jardim Nova Esperança in São José dos Campos-SP (PerCursos, 2024)
The aim of this paper is to analyse the relationship between racism and class prejudice and the lack of sanitation services in informal settlements. The analysis is conducted through a dialogue supported by the theories of Brazilian intellectuals Lélia Gonzalez and Milton Santos, using the case study of Jardim Nova Esperança, located in the municipality of São José dos Campos, SP. The research adopts a dialectical approach and a methodological procedure based on secondary documentation strategies, utilizing statistical sources from public agencies and entities related to sanitation, as well as a bibliographic review of papers and research on the topic. The results reveal the difficulties faced by residents of these settlements, most of whom belong to low-income groups and have Afro-descendant ancestry, in order to access basic sanitation services. This study contributes to a broader understanding of the complex interactions between racism, class prejudice, and the precariousness of basic sanitation, emphasizing the need for concrete measures to address structural disparities in communities experiencing vulnerability. Its conclusions may contribute to the formulation of inclusive policies and the development of strategies aimed at improving the quality of life in these contexts, as well as encouraging future research capable of driving actions to mitigate inequalities and improve sanitation conditions, regardless of individuals' social or ethnic-racial backgrounds.
Keywords: basic sanitation; sanitation services; informal settlements; racism; class prejudice